Tekst: "Hapuskan hutang luar negeri, Bubarkan IMF (wis de buitenlandse schulden, ontbindt de IMF)" (2001)
Tekst: "Hapuskan hutang luar negeri, Bubarkan IMF (wis de buitenlandse schulden, ontbindt de IMF)".